Soil erosion in the marginal upland of Inopacan, Leyte, Philippines - Villamayor, Faustino P.; Asio, Victor B.; Lerios, Arjay O.; Asio, Luz G.; Sabijon, Jessie R. (Annals of Tropical Research, 2017)
There is an urgent need for soil erosion data from marginal uplands in the country. This study evaluated the occurrences of soil erosion in the marginal uplands Inopacan, Leyte. Field soil erosion indicators were assessed in different portions of the study site and erosion plots were established in the corn and sweetpotato fertilizer experiments to measure erosion rates. Field indicators of soil erosion such as rills, cracks across slopes, exposed rocks, thin surface soil and eroded sediments in waterways were common in various parts of the marginal upland studied. Soil erosion rates measured on erosion plots were higher from the corn field than from the sweetpotato field. Application of chicken manure and vermicast resulted in lower soil erosion rates due to improved soil structure. Plots without crop cover gave the highest erosion rates. The degree of soil erosion in the marginal upland can be considered as moderate to severe.